High‐Resolution Measurements of the Cross‐Shock Potential, Ion Reflection, and Electron Heating at an Interplanetary Shock by MMS. Issue 6 (29th June 2019) - Cohen, Ian J.; Schwartz, Steven J.; Goodrich, Katherine A.; Ahmadi, Narges; Ergun, Robert E.; Fuselier, Stephen A.; Desai, Mihir I.; Christian, Eric R.; McComas, David J.; Zank, Gary P.; Shuster, Jason R.; Vines, Sarah K.; et al.
Abstract: The Magnetospheric Multiscale (MMS) spacecraft obtained unprecedented high‐time resolution multipoint particle and field measurements of an interplanetary shock event on 8 January 2018. The spacecraft encountered the supercritical forward shock of a forward/reverse shock pair in the pristine solar wind upstream of the bow shock near the subsolar point as they neared apogee at 25 RE . The high‐time resolution measurements from the four spacecraft, separated by only 20 km, allowed direct measurement of particle distributions revealing evidence of electron heating and near specularly reflected ions. The cross‐shock potential is calculated directly from 3‐D electric field measurements. This is the first reported direct high temporal resolution (<1 s) observation at an interplanetary shock of near specularly reflected ions. Calculation of the cross‐shock potential yields a potential jump significant enough to reflect at least some of the protons from the incident solar wind beam. The cross‐shock potential calculated here is consistent with previous estimations based on particle measurements and numerical/analytical simulations. The ambipolar contribution to the cross‐shock potential calculated from the four‐spacecraft divergence of the electron pressure tensor is somewhat higher than that inferred form the Liouville‐mapped electron energy gain across the shock. Furthermore, the high‐time‐resolution 3‐D electric field measurements reported here reveal small‐scale nonlinear structures embedded in the shock layer that contribute to the nonmonotonic shock transition. Key Points: MMS observed a supercritical IP shock in the upstream pristine solar wind, directly resolving near specularly reflected ions The cross‐shock potential jump calculated from 3‐D E‐field measurements is consistent with the observed electron heating and ion reflection The high‐temporal‐resolution 3‐D electric field measurements revealed small‐scale nonlinear structures embedded within the shock front